The Effect of Strategıc Plannıng Innovatıon and Motıvatıon in Improvıng Organızatıonal Performance - Muhammad Donal Mon (Ekonomis: Journal of Economics and Business, 2022)
The purpose of this study was to examine the effect of the variables of innovation, strategic planning, and motivation on organizational performance. The respondents in this study amounted to 397 respondents consisting of employees of the manufacturing industry in the city of Batam. Data collection was done by distributing questionnaires to respondents via Google form. Analysis of the data in this study using SPSS to see the effect of innovation, strategic planning, motivation on organizational performance. In this study, data analysis will be carried out to test descriptive data, test data quality, test outliers, test classical assumptions and test hypotheses. Based on the results of the research for the three hypotheses, the following results obtained, the innovation variable on organizational performance has a positive and significant effect on organizational performance with a significant 0.036 less than 0.05. Furthermore, the strategic planning variable was not proven in this study to have a positive and significant effect on organizational performance, as indicated by a significance value greater than 0.005, with a Sig value of 0.833. The third hypothesis or motivation variable has a positive and significant effect on organizational performance with a sig value (0.000) less than 0.005.